The Intergenerational Transmission of Welfare Dependency - Monique de Haan; Ragnhild C. Schreiner (Center for Economic Studies and ifo Institute (CESifo), 2018)
There is a strong intergenerational correlation in welfare participation, but this does not imply that parental welfare receipt induces child receipt. While there are a few quasi-experimental studies that provide estimates of the causal effect of parental welfare participation for children from marginal welfare participants, we know very little about intergenerational spillovers of welfare participation onto the children of average welfare participants. By combining rich administrative data from Norway with weak mean-monotonicity assumptions, we estimate nonparametric bounds around the average causal effect of parental welfare participation on children's welfare participation in the general population, as well as the average causal effect for children growing up in welfare-dependent families. We find that these average causal effects are considerably lower than the intergenerational correlation in welfare participation, and substantially below available local average treatment effect estimates in the literature. We further find important differences between intergenerational spillovers of disability insurance and intergenerational spillovers of financial assistance, a traditional means-tested welfare program.
Keywords: H55; I38; J62; 330; welfare dependency; intergenerational spillovers; disability insurance; financial assistance; partial identification